2018
DOI: 10.1002/jcb.28032
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of the lncRNA FER1L4 inhibits paclitaxel tolerance of ovarian cancer cells via the regulation of the MAPK signaling pathway

Abstract: To determine how the lncRNA FER1L4 in ovarian cancer cells influences paclitaxel (PTX) resistance, we examined the expression level of FER1L4 in human ovarian epithelial cell lines IOSE80 and HOSEpiC and human ovarian cancer cell lines OVCAR‐3, Caov‐3, and SKOV3 through RNA isolation and quantitative polymerase chain reaction (qRT‐PCR). SKOV3 cell lines were treated with PTX. The cell survival rate and apoptosis rate of SKOV3 and SKOV3‐PR at different PTX dose levels were evaluated. Next, qRT‐PCR was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
(87 reference statements)
0
24
0
Order By: Relevance
“…Early to 2015, it was reported that high level expression of HOTAIR could induce platinum resistance in ovarian cancer cells by DNA methylation [24]. In addition, researchers found over-expression of lncRNA-FER1L4 could increase the sensitivity of ovarian cancer cells to paclitaxel by inhibiting MAPK signaling pathways [25]. Also, lncRNA-KB-1471A8.2 was reported to be down-regulated in ovarian cancer tissues and chemo-resistant ovarian cancer cells and could act as tumor-suppressor gene by inhibiting the expression of CDK4 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Early to 2015, it was reported that high level expression of HOTAIR could induce platinum resistance in ovarian cancer cells by DNA methylation [24]. In addition, researchers found over-expression of lncRNA-FER1L4 could increase the sensitivity of ovarian cancer cells to paclitaxel by inhibiting MAPK signaling pathways [25]. Also, lncRNA-KB-1471A8.2 was reported to be down-regulated in ovarian cancer tissues and chemo-resistant ovarian cancer cells and could act as tumor-suppressor gene by inhibiting the expression of CDK4 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, miR‐128 inhibited the invasion and modulates chemosensitivity of prostate cancer cells to cisplatin, suggesting that miR‐128 functions as a rational therapeutic strategy for prostate cancer . Paclitaxel is a natural anti‐tumour agent that widely used for the treatment of a variety of tumours, including ovarian cancer . Koh et al reported that miR‐128 suppressed cell proliferation, metastasis, self‐renewal, migration and invasive ability of paclitaxel‐resistant lung cancer stem cells via inhibiting BMI‐1 proto‐oncogene, polycomb ring finger (BMI‐1) and C‐terminal Mucin1 (MUC1‐C).…”
Section: Discussionmentioning
confidence: 99%
“…26 Paclitaxel is a natural anti-tumour agent that widely used for the treatment of a variety of tumours, including ovarian cancer. 27 Koh et al 13 reported that miR-128 suppressed cell proliferation, metastasis, self-renewal, migration and invasive ability of paclitaxel-resistant lung cancer stem cells via inhibiting BMI-1 proto-oncogene, polycomb ring finger (BMI-1) and C-terminal Mucin1 (MUC1-C). A previous study showed that miR-128 level was decreased in cisplatin-resistant epithelial ovarian cancer SKOV-3/CP cells compared with that in parental SKOV-3 cells, and miR-128 overexpression suppressed cisplatin resistance in SKOV-3/CP cells.…”
Section: Discussionmentioning
confidence: 99%
“…In OC, FER1L4 is expressed at low levels compared to normal ovarian epithelial cells and, at even lower levels in paclitaxel-resistant cell lines. Transfection with FER1L4 led to MAPK pathway suppression and restored the sensitivity to paclitaxel, indicating an important role in the development of resistance (177). Overall, PTEN-AKT-mTOR and MAPK are major cancer driver pathways deeply…”
Section: Lncrnas Involved In the Taxane Resistancementioning
confidence: 96%